The complete chloroplast genome and phylogenetic analysis of Veratrum mengtzeanum Loes. F. (Liliaceae). Issue 2 (3rd July 2019) - Han, Li-Jun; Liu, Ying-Ying; Zhang, Ying-Min; Yang, Cong-Wei; Qian, Zi-Gang; Li, Guo-Dong
Abstract: Veratrum mengtzeanum Loes. F. is a medicinal plant belonging to the genus Veratrum (Liliaceae). In the present study, we assembled and characterized the complete chloroplast (cp) genome of this species. The chloroplast genome is 152, 051 bp in length, with one large single copy (LSC) region and one small single copy (SSC) region of 82, 112 bp and 17, 544 bp, respectively; two inverted repeat (IR) regions of 26, 198 bp. It contains 131 annotated genes, including 85 protein-coding genes (PCGs), 38 transfer RNA (tRNA) genes, and 8 ribosomal RNA (rRNA) genes. Phylogenetic analysis indicated that V. mengtzeanum was closely related to Veratrum japonicum with 100% bootstrap value.